Emerging roles for cyclooxygenase‐2 in gastrointestinal mucosal defense - Wallace, John L; Devchand, Pallavi R (British journal of pharmacology, 2005)
The development of selective inhibitors of cyclooxygenase‐2 (COX‐2) was based on the concept that this enzyme played little, if any, role in modulating the ability of the gastrointestinal (GI) tract to resist and respond to injury. There is now overwhelming evidence that this is far from true. Indeed, COX‐2 mediates several of the most important components of ‘mucosal defense’, contributes significantly to the resolution of GI inflammation and plays a crucial role in regulating ulcer healing. COX‐2 also contributes to long‐term changes in GI function after bouts of inflammation. British Journal of Pharmacology (2005) 145, 275–282. doi:10.1038/sj.bjp.0706201